Pengaruh Variasi Konsentrasi Nanokomposit CoFe₂O₄/Cdots terhadap Karakteristik Gugus Fungsi, Sifat Optik, dan Morfologi yang Disintesis melalui Pendekatan Green Synthesis - Angelika Ramona Putri Hasibuan; Edi Suharyadi; Suprihatin; Posman Manurung (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2026)
CoFe2O4/Cdots nanocomposites have been successfully synthesized by combining CoFe2O4 synthesized from Moringa oleifera (MO) extract and Cdots synthesized from watermelon rind. CoFe2O4/Cdots nanocomposites were synthesized using a green synthesis method. This study began with the synthesis of MO, CoFe2O4, Cdots, then CoFe2O4/Cdots. Thus, CoFe2O4/Cdots-10, CoFe2O4/Cdots-20, and CoFe2O4/Cdots-30 were obtained, each based on variations in the concentration of Cdots to CoFe2O4, that is 10, 20, and 30 ml. After the synthesis process, characterization was carried out using FTIR, UV-Vis and TEM. The results of FTIR testing on nanocomposites showed the presence of typical functional groups of Cdots and typical functional groups of CoFe2O4. The combination of both produces a wave number shift caused by the emergence of new bonds between Cdots and CoFe2O4. The results of UV-Vis testing show that the addition of Cdots does not significantly affect the absorbance, but there is a shift in the absorbance peak to the left along with the addition of Cdots variations. This causes the band gap energy value to increase. The results of TEM testing show that the morphology of both samples is semi-spherical and tends to agglomerate along with the addition of Cdots. However, the addition of Cdots concentration results in a smaller particle diameter and is relatively more uniform. This results in a larger surface area and is effective for use in various applications. The results of Selected Area Electron Diffraction (SAED) show that the diffraction ring with the presence of a lattice is still in the CoFe2O4 phase. Kata kunci: CoFe₂O₄/Cdots nanocomposite, green synthesis, FTIR, UV–Vis, TEM, optical properties, morphology.